Management strategies and cost effectiveness in the prevention of cervical cancer - Smita R Prasad (Dove Medical Press, 2009)
Smita R PrasadUniversity of Kentucky, College of Public Health, Lexington, KY, USAAbstract: This paper introduces the burden of cervical cancer and the primary and secondary preventative interventions currently available, and provides an overview of the bivalent and quadrivalent human papillomavirus (HPV) vaccines. A brief account of the virology and the clinical efficacy of both is given. Examinations of the two main types of cost analyses, cost-effective and cost-benefit, as well as examples, are presented in addition to the possible impact these analyses and further economic models will have on budget and policy making decisions. In general, most cost analyses provide support for the implementation of primary prevention strategies, HPV immunization, in conjunction with cervical cancer screening programs. Vaccination against HPV, therefore, is a cost-effective cervical cancer prevention mechanism.Keywords: cervical cancer, human papillomavirus, HPV